Sanksi Pidana Tentang Pencemaran Nama Baik Melalui Media Internet - Sri Herlina (Jurnal Penegakan Hukum Indonesia, 2022)
Later, there were reports about defamation allegations by various parties. The causes vary, ranging from writing on mailing lists, forwarding emails, reporting corruption, reporting events in the media, revealing research results, and a series of other actions. This study aims to describe the legal arrangements regarding defamation in Indonesian criminal law and criminal sanctions for perpetrators of criminal defamation through the internet media. The type of research used is normative legal research, that is, research that focuses on norms and this research requires legal materials as the main data. Meanwhile, the nature of the research that the author uses is research that is descriptive analytical in the sense that all legal materials that the author gets will be described and described and then analyzed. The results showed that: The regulation of defamation law as stipulated in the Criminal Code interprets that, the main element of the criminal act of defamation is the intention to attack a person's honor or good name so that the general public knows about it, as well as the absence of elements for the public interest and / or self-defense in it. This criminal act of defamation is also a complaint, where a person who defames another person cannot be prosecuted if there is no complaint from the person who has been defamed, as stipulated in Article 319 of the Criminal Code. As for the criminal liability for perpetrators of criminal defamation in the ITE Law, this is contained in article 51 paragraph (2) of Law Number 11 of 2008 concerning Electronic Information and Transactions in which a person who disseminates electronic information that contains insults and/or defamation and results in losses to others will be subject to a maximum prison penalty of 12 years and/or a maximum fine of 12 billion rupiah.